Novel Mutations Associated With Various Types of Corneal Dystrophies in a Han Chinese Population - Zhang, Jing; Wu, Dan; Li, Yue; Fan, Yidan; Chen, Huiyu; Hong, Jiaxu; Xu, Jianjiang (Frontiers in Genetics, 2019)
Aims: To study the genetic spectra of corneal dystrophies (CDs) in Han Chinese patients using next-generation sequencing (NGS). Methods: NGS-based targeted region sequencing was performed to evaluate 71 CD patients of Han Chinese ethnicity. A custom-made capture panel was designed to capture all coding exons and untranslated regions plus 25 bp of intronic flanking sequences of 801 candidate genes for eye diseases. The Genome Analysis Tool Kit Best Practices pipeline and an intensive computational prediction pipeline were applied for the analysis of pathogenic variants. Results: We achieved a mutation detection rate of 59.2% by NGS. Eighteen known mutations in CD-related genes were found in 42 out of 71 patients, and these cases showed a genotype–phenotype correlation consistent with previous reports. Nine novel variants that were likely pathogenic were found in various genes, including CHST6, TGFBI, SLC4A11, AGBL1, and COL17A1. These variants were all predicted to be protein-damaging by an intensive computational analysis. Conclusions: This study expands the spectra of genetic mutations associated with various types of CDs in the Chinese population and highlights the clinical utility of targeted NGS for genetically heterogeneous CD.